Search for top and bottom squarks from gluino pair production in final states with missing transverse energy and at least three b-jets with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2012)
This letter reports the results of a search for top and bottom squarks from gluino pair production in 4. 7 fb -1 of pp collisions at √s =7 TeV using the ATLAS detector at the LHC. The search is performed in events with large missing transverse momentum and at least three jets identified as originating from a b-quark. Exclusion limits are presented for a variety of gluino-mediated models with gluino masses up to 1 TeV excluded. © 2012 CERN for the benefit of the ATLAS collaboration.